Usaha Budi Daya Pepaya Bangkok dengan Sistem Lahan Sewa - Agung Wijayanto; . Suryahadi; Amiruddin Saleh (Institut Pertanian Bogor, 2012)
One area of agribusiness that has good prospects for development is the cultivation of papaya farming Bangkok, because the market demand is still huge, rapid investment payback period, the price is relatively stable, and continuous harvest throughout the year. The market opportunity is still wide open, because the supply is currently still lacking. Located in the Village Prangkoan, Mertoyudan District, Magelang regency, Central Java. The purpose of this study was to (1) analyze the feasibility of Papaya Bangkok cultivation with his own land and rent system, (2) business feasibility analysis Papaya Bangkok cultivation with leased land and the cultivation of papaya integration model of Bangkok's most profitable for entrepreneurs to raise Papaya Bangkok cultivation. Quantitative analysis carried out to analyze the feasibility of the financial aspects using the criteria of NPV, IRR, Gross benefit and Cost Ratio, Sensitifitas, and BEP analysis. NPV value of aquaculture in their own land is higher at Rp103,793,371.93, while cultivating the land lease Rp60,069,785.97. This shows that the net benefits received from cultivation in their own land is greater than in the land lease. Judging from the value of Gross IRR and B/C, indicating that the value of Gross IRR and B/C for all the cultivation is > 0, so that both are good at cultivating their own land or on leased land eligible to run. When viewed from the BEP, the BEP for the cultivation of the land it self is 1548 units and Rp6,190,661, while for the cultivation of the land rent is 6972 units and Rp10,457,406.67. Comparison of financial feasibility between the two tampat cultivation shows that of both types of businesses, the cultivation of the land itself is a more viable business cultivated. It can be seen from the financial eligibility criteria of the cultivation the land itself has a better value